An immunocompetent mouse model revealed that congenital Zika virus infection disrupted hippocampal function by activating autophagy - Wei Yang; Zhan-Zhan Bian; Zhe Li; Yi-Teng Zhang; Li-Bo Liu; Jia-Tong Chang; Dan Li; Pei-Gang Wang; Jing An; Wei Wang (Emerging Microbes and Infections)
Congenital Zika virus (ZIKV) infection significantly affects neurological development in infants and subsequently induces neurodevelopmental abnormality symptoms; however, the potential mechanism is still unknown. Therefore, in order to effectively intervene in neurodevelopmental abnormalities in infected infants, it is necessary to identify the main brain regions affected by congenital infection. In this study, we constructed a congenital ZIKV-infected murine model using immunocompetent human STAT2 knock-in mice, which presented long-term neurodevelopmental abnormalities with abnormal neurodevelopmental symptoms. We found that the hippocampus, which regulates cognitive behaviour and processes spatial information and navigation, was the main brain region affected by congenital infection and that hippocampal cells were more prone to autophagy during the growth period of these mice at the transcriptional and pathological levels. These findings highlighted that congenital ZIKV infection could interrupt hippocampal function by activating autophagy, thus providing a theoretical basis for the clinical treatment of congenital ZIKV-infected infants.